Relationship Between Sleep Quality and Quality of Life in Hemodialysis Patients: A Literature Review - Calisanie, Nyayu Nina Putri; Gunadi, Mochamad (KnE Life Sciences, 2021)
Poor sleep quality can worsen hypertension, type 2 diabetes and obesity, thereby increasing the incidence of cardiovascular disease, as well as accelerating the progression of end-stage kidney disease and reducing survival rates. In hemodialysis patients, many factors affect the patient’s quality of life start from a psychological, physiological, social, and economic perspective can decreased the patient’s quality of life. To know about the relationship between sleep quality and quality of life in hemodialysis patients, this study uses a literature review method, based on the results of an article published within the last 10 years. From 5 journals that met the criteria, it was found that there was relationship between sleep quality and quality of life. There is a significant relationship between sleep quality and quality of life in hemodialysis patients. Keywords: Hemodialysis, Sleep quality, Quality of life.